2019
DOI: 10.1115/1.4043329
|View full text |Cite
|
Sign up to set email alerts
|

The Present Challenge of Transonic Compressor Blade Design

Abstract: The flow through a transonic compressor cascade shows a very complex structure due to the occurring shock waves. In addition, the interaction of these shock waves with the blade boundary layer inherently leads to a very unsteady flow behavior. The aim of the current investigation is to quantify this behavior and its influence on the cascade performance as well as to describe the occurring transonic flow phenomena in detail. Therefore, an extensive experimental investigation of the flow in a transonic compresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, all major unsteady phenomena were predicted just in a narrow mass flow range near the stability limit for the large tip clearance cases (Gap 2 and Gap 3). It has been reported that induced vortex, 20 vortex breakdown, 24 self-induced unsteadiness 31 or fluctuation of shock wave 32 could be the source of unsteady flow behavior in axial compressor stages. In this section, necessary condition for the inception of the unsteadiness in the tip region of the low-reaction rotor will be discussed.…”
Section: Resultsmentioning
confidence: 99%
“…However, all major unsteady phenomena were predicted just in a narrow mass flow range near the stability limit for the large tip clearance cases (Gap 2 and Gap 3). It has been reported that induced vortex, 20 vortex breakdown, 24 self-induced unsteadiness 31 or fluctuation of shock wave 32 could be the source of unsteady flow behavior in axial compressor stages. In this section, necessary condition for the inception of the unsteadiness in the tip region of the low-reaction rotor will be discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the last source of uncertainty relates to the effects the unsteady flow might have on the measured steady performance. This is especially relevant when comparing these results to CFD-(U)RANS simulations that have been shown to not capture the nature and extent of these effects for the given application [2]. This discrepancy is recognized, though the comparison is performed because RANS remains the automatic choice for design purposes, as done for the design of the TCTA.…”
Section: Limitations Of the Experimental Configurationmentioning
confidence: 99%
“…The presence of an inherently unsteady shock structure that impacts the entire flow field, its potential strong interaction with the boundary layer, and cascade-specific operating conditions, such as choking at unique incidences [1], are just some of the possible sources of significant discrepancies that (U)RANS users need to be aware of. In practice, designers are forced to apply undesirably high design margins, as explained in recent work [2].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, researchers are focused on improving the performance of centrifugal compressors by optimizing blade geometry parameters such as camber, thickness, angle, and profile shape, which directly impact their aerodynamic characteristics [4]. A well-designed blade geometry can significantly enhance the efficiency of a centrifugal compressor.…”
Section: Introductionmentioning
confidence: 99%